الفتاوى الشاذة وتطبيقاتها المعاصرة : دراسة نقدية - فرج، صلاح الدين طلب سلامة (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This research aims at defining the concept of anomaly in Fatwa and indentifying the cases where Fatwa becomes anomalous. The researcher uses the inductive research approach to examine the topic. Using the analytic approach, the researcher illustrates the meaning of fatwa, its legitimacy and related commandments, classifies the scholars' opinions on the different issues, evaluates them, shows which of them is most preferred, investigates whether the anomaly can disappear from the fatwa when time changes, and highlights the modern scholars' point' of view regarding the anomalous fatwa. The comparative approach has been applied to compare the opinions on the different issues and emphasize the similarities and differences between the various research terms. Through the analytic approach, examples of the anomalous modern fatwa are displayed with the reasons behind their anomaly, the scholars' opinions regarding those fatwa as well as the means to treat that anomaly. Last but not least, the research arrives at the findings where the most important are the anomalous fatwa can be defined as “the one that is built on a weak perception or interpretation, or violated the Sharia objectives in a certain age”, it can be issued either by a scholar or a person who pretends scholarship, and it may be issue by a Mujtahid as he is not infallible. Then, the researcher collected some of the modern scholars' anomalous fatwa such as Sheikh Tantawi's fatwa that permits Islamic banking and financial benefits, and the fatwa of Dr. Ali Jumah that prohibits female circumcision. Nowadays fatwa requires further regulation, for instance to train qualified Mufti and prevent non-specialists from exercising fatwa